2010
DOI: 10.1111/j.1365-2966.2010.16983.x
|View full text |Cite
|
Sign up to set email alerts
|

Super star clusters in Haro 11: properties of a very young starburst and evidence for a near-infrared flux excess

Abstract: We have used multiband imaging to investigate the nature of an extreme starburst environment in the nearby Lyman break galaxy analogue Haro 11 (ESO 350−IG038) by means of its stellar cluster population. The central starburst region has been observed in eight different high‐resolution Hubble Space Telescope (HST) wavebands, sampling the stellar and gas components from UV to near‐infrared. Photometric imaging of the galaxy was also carried out at 2.16 μm by NaCo AO instrument at the ESO Very Large Telescope. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
283
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(306 citation statements)
references
References 76 publications
20
283
3
Order By: Relevance
“…Thus the dominating hydrogen phases could be H + and H 2 , providing more favourable conditions for escape than in normal galaxies where H I serves as an effective shield for the LyC radiation. Bergvall et al (2006) also investigated the ionizing stellar population and found signatures of Wolf Rayet stars in the optical as well as P Cygni profiles in the far-UV, revealing the presence of O supergiants and an ongoing burst or a burst that has only very recently ended, in agreement with the ages derived in Adamo et al (2010).…”
Section: Haro 11supporting
confidence: 66%
See 1 more Smart Citation
“…Thus the dominating hydrogen phases could be H + and H 2 , providing more favourable conditions for escape than in normal galaxies where H I serves as an effective shield for the LyC radiation. Bergvall et al (2006) also investigated the ionizing stellar population and found signatures of Wolf Rayet stars in the optical as well as P Cygni profiles in the far-UV, revealing the presence of O supergiants and an ongoing burst or a burst that has only very recently ended, in agreement with the ages derived in Adamo et al (2010).…”
Section: Haro 11supporting
confidence: 66%
“…Haro 11 has a complex morphology with three main star-forming knots and seems to be dynamically unrelaxed, remniscent of a merger event (Östlin et al 2001). The knots each contain numerous super star clusters, for which Adamo et al (2010) derived young ages, between 1 and 40 Myr and masses between 10 3 and 10 7 M . Haro 11 is also found to have a low metallicity, with an oxygen abundance 12+log(O/H) = 7.9 (Bergvall & Östlin 2002), and a surprisingly low H I content.…”
Section: Haro 11mentioning
confidence: 99%
“…It has no neighbors but morphologically and kinematically the galaxy appears to be involved in a merger [116,117,121]. It has a gas consumption timescale of ∼ 100 Myr a birthrate parameter b ∼ 15 and is involved in a vigorous global starburst, producing a large number of super star clusters [1]. The cluster formation efficiency is about 10 times higher than in large spiral galaxies.…”
Section: Starburstsmentioning
confidence: 99%
“…The major difference between the bursting state and the normal one seems rather to be the mode of star formation, the tendency for stars to form in super star clusters (SSCs) [e.g. 1,111] and possibly switch to a flatter IMF [45,139,164].…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by the contribution of neighbouring sources as well as the nebular emission from nearby (often related) ionised gas which is stronger at redder wavelengths (e.g., Reines et al 2010;Adamo et al 2010a). Models that include nebular emission can explain some of this excess near-IR emission, however, for some clusters the models cannot account for the additional flux.…”
Section: Discussionmentioning
confidence: 99%